Design and implementation of a wireless sensor network applied to motion capture - Afonso, José A. (2011)
This paper describes the development of a wireless sensor network prototype and its application in a motion capture system based on inertial and magnetic sensors. The system presents a portable and modular architecture and allows the monitoring of several users at the same time using a single wireless network. The target application requires the wireless sensor network to operate efficiently under high loads, since it generates data intensive traffic and needs to support a high number of sensor modules. Other requirements imposed by the application are real-time operation and reliable data delivery. In order to provide the quality of service required by the application, an enhanced version of the LPRT medium access control protocol was developed and implemented in devices compliant with the IEEE 802.15.4 standard at the physical layer. Simulation results show that the proposed modifications improve the performance of the protocol. The implementation of the protocol is validated through the experimental results presented.